Do calcareous soils affect morphological and physiological characteristics of maize hybrids and their iron efficiency? - Thyagarajan, Chitdeshwari; Rajasekaran, Ravikesavan; A.P., Sivamurugan; Alagarswamy, Senthil (Plant Science Today, 2025)
Maize (Zea mays L.) is the third most cultivated cereal crop in the world after wheat and rice. Soil calcareousness is the key growth limiting factor causing a substantial decline in plant growth and yield in many arid and semiarid regions globally. This study aimed to understand the variability in morphological and physiological traits among maize hybrids as well as their iron (Fe) efficiency on calcareous soils. Five ruling maize hybrids [COH (M) 6, COH (M) 7, COH (M) 8, COH (M) 9 and COH (M) 10] and their six inbreds [UMI 1200, UMI 1201, UMI 1205, UMI 1210, UMI 1220, and UMI 1230] were evaluated on three calcareous soils having various free CaCO3 content (6.23 to 17.3%) with and without Fe supply. The experiment was carried out in the greenhouse of the Department of Soil Science, Tamil Nadu Agricultural University, Coimbatore, in 2019. Soil calcareousness reduced the morphological and photosynthetic parameters of all the maize hybrids, and the reduction was more in highly calcareous soils (17.3%). Significant variation in Fe efficiency among maize hybrids was observed and shows good association with physiological and photosynthetic characteristics. The maize hybrids COH (M) 6, COH (M) 8, and COH (M) 7 record higher growth attributes, photosynthetic parameters, and active Fe content with better Fe efficiency. Lower Fe efficiency was noted with inbreds UMI 1230 and UMI 1220. The study showed that maize hybrids and their inbreds were sensitive to higher soil calcareousness, but the magnitude of differences varied with genotypes.